Efficacy of intravenous hydration during extracorporeal shock wave lithotripsy in improving ureteral stone treatment success rate. (26th February 2022) - Cheng, Weiming; Chiu, Yi‐Chun; Fan, Yu‐Hua; Chang, Chang‐Chi; Kao, Kuo‐Wei
Abstract : Objective: The treatment efficacy of extracorporeal shock wave lithotripsy for urolithiasis depends on several factors. We aimed to evaluate the impact of intravenous hydration during shock wave lithotripsy on stone treatment success rate in patients with ureteral stones. Methods: We retrospectively evaluated patients with ureteral stones <2 cm in diameter treated with extracorporeal shock wave lithotripsy at two sites. Patients from one of the sites received intravenous hydration with 500 mL of 0.9% NaCl. Stone treatment success status was defined as stone‐free or residual ureteral stones <0.4 cm in diameter 1 month after the procedure. Predictive factors associated with treatment success were evaluated using univariate and multivariate logistic regression. Results: Overall, 146 consecutive patients with ureteral stones were included. Eighty (54.8%) patients received intravenous hydration. The overall stone treatment success rate was 66.4%. Those with intravenous hydration during the shock wave lithotripsy had significantly smaller stone size, lower serum creatinine levels, lower rate of alpha‐blockers use, and higher rate of nonsteroidal anti‐inflammatory drug use. Upon multivariate analysis, stone treatment success status postprocedure was significantly associated with stone size (odds ratio 4.118, 95% confidence interval 1.920–8.832, P  < 0.0001) and intravenous hydration during the procedure (odds ratio 2.475, 95% confidence interval 1.176–5.208, P  = 0.017). Conclusion: Besides small ureteral stone size, concomitant intravenous hydration with 500 mL of normal saline during extracorporeal shock wave lithotripsy was significantly associated with subsequent stone passage. Administering 0.9% NaCl may be a simple and effective measure to improve the treatment efficacy of extracorporeal shock wave lithotripsy.